Proposed Changes to Kaupás Logistics with the Aim of Reducing Kaupás Cost - Bjornsson, Halldor (2009)
Kaupás has for a number of years worked on improving its operation. At the same time its logistics function has been largely neglected, leaving its management up to instinct rather than knowledge. This situation is not only true for Kaupás but for most of the grocery industry in Iceland, leaving suppliers in a similar situation. The dissertation will try to shed light on Kaupás’ logistics function in order to locate areas that need attention and improvement. With the help of the literature review, a general overview of logistics functions is provided. The literature review helps when identifying areas in which to focus improvements as well as deciding which methods of improvement to use. An analysis of collected data and interviews performed will be coupled with the literature review to identify areas within Kaupás logistics function that need improvement and which methods should be used to improve the function. Improvement recommendations will be made and financial return will be calculated in as much detail as possible.